The Effectiveness of Digital Marketing Strategies in Attracting Generation Z in the Era of Social Media - Muhammad Sufianur; Hana Rona (IECON: International Economics and Business Conference, 2025)
This study discusses the effectiveness of digital marketing strategies in attracting the attention of Generation Z, a demographic group that is very familiar with technology and social media. Strategy digital marketing effectively attracts the attention of Gen Z in the social media era by understanding their unique characteristics, such as appreciating brand value and impact, emphasizing authenticity and personalization, and being proficient in using technology. With the AIDA theory approach and the concept of influencer and content marketing, this study analyzes the most successful platforms, content, and digital approaches in building engagement with Gen Z. This research was conducted by a mixed-method, using questionnaires and interviews. Results show that authentic approaches, the use of micro-influencers, as well as short, interactive content such as TikTok videos and Reels are highly effective in reaching and influencing Generation Z. By understanding Gen Z's digital behavior and using the right digital marketing strategy, businesses can increase brand awareness, increase engagement, and ultimately increase sales. Therefore, the effectiveness of digital marketing strategies in attracting the attention of Gen Z depends heavily on the ability of businesses to understand adaptation to their needs and preferences..